The pathophysiology of endothelial function in pregnancy and the usefulness of endothelial markers - Slavik, Ludek; Prochazkova, Jana; Prochazka, Martin; Simetka, Ondrej; Hlusi, Antonin; Ulehlova, Jana (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2011)
AIM: The aim of this study was to assess coagulation markers of endothelial damage and examine new markers of endothelial activation such as matrix metalloproteinases (MMPs) in a group of healthy pregnant women. Matrix metalloproteinase (MMP)-2, in particular, plays a major role in the degradation of the extracellular matrix confirming its essential function in both the survival (angiogenesis) and death of endothelial cells. Detection of specific coagulation factors, mainly released from the vascular endothelium such as vWF, sTM (soluble thrombomodulin) and ePCR (endothelial protein C receptor) and factors dependent on endothelial activation such as t-PA and PAI-1, could provide information on possible endothelial dysfunction and help differentiate pregnant patients with an altered thrombotic state. METHODS: Healthy pregnant women underwent complete assessment for endothelial damage (as vWF, vWF activity, sTM, ePCR, EMP, MMP-2, MMP-9 and TIMP-2) using the ELISA and other methods. RESULTS AND CONCLUSIONS: The results show that endothelial activation during pregnancy is different from that in other pathological conditions involving endothelial damage and typically characterized by higher levels of both coagulation endothelial markers and MMPs. In pregnancy, changes in extracellular matrix composition and matrix metalloproteinase activity also occur and promote vascular remodeling but, only in the uterus. Predisposing risk factors for epithelial dysfunction, and vascular mediators associated with vascular remodeling must be assessed from concentrations in whole blood. The levels of MMPs are not increased in the circulation and the local situation in the uterus cannot be monitored this way. However, MMP-2 processes and modulates the functions of many other vasoactive and pro-inflammatory molecules including adrenomedullin, big endothelin-1, calcitonin gene-related peptide, CCL7/MCP-3, CXCL12/SDF-1, galectin-3, IGFBP-3, IL-1 Beta, S100A8, and S100A9. These molecules represent new potential molecular markers of endothelial damage during pregnancy.
Keywords: Pregnancy Complications; komplikace těhotenství; těhotenství; Endothelium, Vascular; koagulační faktory; tkáňové inhibitory metaloproteinas; Matrix Metalloproteinases; Extracellular Matrix; Tissue Inhibitor of Metalloproteinases; ženské pohlaví; Blood Coagulation Factors; Humans; Pregnancy; biologické markery; cévní endotel; Biomarkers; Female; extracelulární matrix; lidé; matrixové metaloproteinasy